Implementasi Augmented Reality sebagai media pembelajaran perangkat Internet of Things dengan metode Marker Based Tracking: Implementation of Augmented Reality as a Learning Media for Internet of Things Devices with Based Marker Tracking Method - Ragil Galuh Pangita; Royana Afwani; Ahmad Zafrullah Mardiansyah (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2023)
Learning media is an important factor in the learning process. By using the right learning media, someone can easily understand what is being studied. Currently, augmented reality is a technology that is being developed in various fields, one of which is in the field of education. Augmented reality can be an alternative to effective and interactive learning media because augmented reality can combine 2D or 3D objects into a real environment. To learn about the internet of things devices, currently, students can only learn through books or do the hands-on practice. If an error occurs during practice, it can cause damage to the internet of things device. By utilizing augmented reality technology, a new learning media is created by combining 3D objects from internet of things devices into the real environment. This learning media application was tested using the Blackbox and Mean Opinion Score methods. Blackbox testing shows that all functions have been running properly by the functional requirements that have been defined. Testing using the Mean Opinion Score shows that the average student respondent's assessment of the application is stated to strongly agree as much as 60.3% and agree as much as 35.3%.